Program GEMAS (Gerakan Masyarakat Sehat): Upaya Deteksi Dini dan Peningkatan Kesadaran Penyakit Tidak Menular - Surtania; Naswa Chikita Ayunandri; Marista Milani; Fany Rahma Sari; Victor Bernando Missionary (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2025)
Non-communicable diseases (NCDs) such as hypertension, diabetes, and dyslipidemia have become a major health burden in Indonesia, with many cases remaining undiagnosed due to their asymptomatic nature. Early detection through community screening is a key prevention strategy. Objective: This community service activity, 'Gerakan Masyarakat Sehat' (GEMAS), aimed to conduct health screenings for the early detection of NCD risk factors among the residents of Jembrak Village, Semarang Regency. Methods: The activity was carried out on June 14, 2025, by lecturers and students from the Faculty of Health Sciences, Satya Wacana Christian University. Free examinations included blood pressure, random blood glucose, cholesterol, and uric acid levels for 29 residents. Results: The findings revealed a high prevalence of risk factors: 51.8% of participants had above-normal blood pressure (prehypertension and hypertension), 10.7% were identified with prediabetes, 39.2% had dyslipidemia, and 37.9% suffered from hyperuricemia. Many participants exhibited a clustering of more than one risk factor. Conclusion: This screening program effectively unveiled the hidden burden of NCDs within the community. It underscores the importance of proactive early detection programs, with referral to the local primary health center (Puskesmas) being a crucial step for further management and complication prevention.